The role of individual variables as antecedents of entrepreneurship processes: Emotional intelligence and self-efficacy - López-Núñez, María Inmaculada; Rubio-Valdehita, Susana; Díaz-Ramiro, Eva M. (Frontiers in Psychology, 2022)
Currently, entrepreneurship is a priority for economic, social, and technological growth. Therefore, the interest in understanding entrepreneurship processes has increased significantly. Individual variables play a fundamental role, and academic research has pointed out the influence of emotional intelligence in entrepreneurial processes; however, its relationship with other interpersonal processes and individual variables, such as personality and self-efficacy, has not been extensively studied. The aim of this research was to analyze the relationship among emotional intelligence, self-efficacy, and entrepreneurial intention, controlling for the effects of personality, gender, and age. Multiple hierarchical regression analyses were applied through a questionnaire survey of 1,593 college students to test the relationship between the constructs in the model. The results show that the personality traits are associated with entrepreneurial self-efficacy, emotional intelligence positively influences entrepreneurial intention, and self-efficacy mediates the relationship between emotional intelligence and entrepreneurial intention. Practical implications for training programs are examined, and future lines of research were discussed.